Data Warehouse Schemas using Multidimensional Data Model for Retail - Shobirin, Kheri Arionadi; Iskandar, Adi Panca Saputra; Swamardika, Ida Bagus Alit (International Journal of Engineering and Emerging Technology; Vol 2 No 1 (2017): January - June, 2017)
A data warehouse are central repositories of integrated data from one or more disparate sources from operational data in On-Line Transaction Processing (OLTP) system to use in decision making strategy and business intelligent using On-Line Analytical Processing (OLAP) techniques. Data warehouses support OLAP applications by storing and maintaining data in multidimensional format. Multidimensional data models as an integral part of OLAP designed to solve complex query analysis in real time.